Introduction of Motivational Technologies as an Effective Instrument Human Resources Management ("Journal "U". Economy. Management. Finance.", 2023)
The article discusses approaches to personnel motivation through the use of various motivational technologies, the importance of choosing the right motivation system to influence the spiritual, moral, socio-psychological, information, communication and material aspects of employees' activities. Determined the place of motivational technologies, as a lever of motivation, in the organization's human resources management system.
Keywords: motivation; motivational technologies; human resources management system; stimulation of job activity